Perkuatan Soil Nailing pada Lereng Singajaya Garut - Champernic Tarakashima; Athaya Zhafirah; Dicky Muhamad Fadli (Jurnal Konstruksi, 2023)
The landslide natural disaster that hit the slopes of Cigunung Singajaya Garut caused road access to Cihurip District to be cut off. This research aims to determine the safety value of slopes and plan reinforcement that can increase the safety value of slopes. Slope strengthening with soil nailing was used in this research with variations in slope angles of 10ï‚°, 15ï‚°, and 20ï‚° and variations in nail bar length by the same amount, namely 8 m, 10 m, and 12 m. The soil nailing method used in this research. Slope stability analysis of the Bishop method and GeoStudio Slope/W student version. The results of the slope stability analysis before strengthening produced a safety factor value, using the Bishop method, it was 0.273 and analysis using GeoStudio Slope/W student version was 0.201. The results of the slope stability analysis after strengthening with variations in slope angle and nail bar length produced different safety factor values, namely 1.286 for an angle of 10Âº; 2,195 for 15Âº angle; and 1.540 for a 20Âº angle. The predicted results of soil nailing cost budget planning with a planning area of ”‹”‹1321 m2 is IDR 5,513,664,027.12.